Medium Duration Threshold Patterned Laser PhotoÂ coagulation for Panretinal Photocoagulation - Habsyiyah Habsyiyah; Elvioza Elvioza; Andi Arus Victor; Ari Djatikusumo; Gitalisa Andayani; Anggun Rama Yudantha (Majalah Oftalmologi Indonesia, 2015)
Background: Laser photocoagulation is a crucial therapy for numerous retinal diseases. Laser can be delivered with different machines and modalities (slit lamp, endolaser, indirect laser) at different wavelengths (532 to 812 nm) with varying parameters (power, spot size, duration, number of spots). New developments using semi automatic pattern delivery of retinal laser burns which use smaller amounts of energy and shorter duration have been reported. This literature review is conducted to review various published article that reported efficacy, safety, and duration of medium duration threshold patterned (MDTP) laser photocoagulation.Methods: This literature review was conducted from the Pubmed (NLM) database and Ophsource using the keyword panretinal photocoagulation, and Pascal or medium threshold or short exposure. The inculsion criteria of this review were all of studies which reported the use of medium duration threshold patterned which was applied as panretinal photocoagulation (PRP).Results: Parameter used in MDTP laser were as follow, spot size was between 200 to 400 Î¼m, duration was 20-30 ms, and average laser power was more than 200 to 630 mV. Compare to standard laser treatment, power used in MDTP laser were higher.Conclusion: Medium duration threshold patterned laser photo-coagulation is as effective as conventional laser. MDTP laser can preserve the retinal sensitivity/visual field, also offers less pain and discomfort and safe to perform full scatter PRP in single sittingÂ Keywords: medium duration threshold patterned laser; panretinal photocoagulation